MANAJEMEN KOMUNIKASI DAN NEGOSIASI PENDIDIKAN ISLAM MULTIKULTURAL - Ansori; Nurjanah; Kasful Anwar (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This paper discusses communication and negotiation management in Islamic education within the context of a multicultural society. Amid Indonesia’s rich diversity of cultures, ethnicities, and religions, Islamic education faces the challenge of creating an inclusive, fair, and harmonious learning environment. Communication is not merely understood as the transmission of information but also as a medium for building cross-cultural understanding rooted in Islamic values such as ta’aruf (mutual recognition), tasamuh (tolerance), and tawazun (balance). Meanwhile, negotiation serves as a strategic instrument for resolving conflicts, fostering deliberation (musyawarah), and maintaining social justice in educational interactions. Through theoretical perspectives and implementation analysis, this paper highlights the importance of teacher training, the development of responsive educational policies, and the reinforcement of inclusive curricula. With effective communication and negotiation management, Islamic educational institutions are expected to become pioneers in nurturing a generation that is tolerant, dialogical, and appreciative of diversity as a national asset.